(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the opinions of our country and foreign scientists are mentioned about the theoretical foundations of the emergence of the Temuri state in Uzbekistan. The emergence of the fall of the Mongol Empire, particularly the fragmentation of the Chaghatai Khanate in Central Asia, created a power vacuum. The weakening of Mongol authority facilitated the rise of regional powers, including the Timurids. Timur (Tamerlane), a descendant of Genghis Khan, capitalized on the instability. By consolidating power through military conquests, strategic alliances, and administrative reforms, Timur established the Timurid Empire. His ability to harness both the remnants of Mongol and Persian influences played a crucial role in his success.